Annual Plan Proposals 2006-07 Government of Kerala - Planning Commission (Planning Commission, 2006)
Promotion of farming systems approach and watershed management, group farming, modernization of agriculture, restructuring of agricultural extension, improved service delivery systems, value addition, integrated pests and disease management, promotion of credit flow to agriculture, promotion of micro enterprises, creation of disease free zone for cattle, stock up gradation, conservation and development of indigenous breeds, up gradation of infrastructure for marketing and quality control, development of inland fisheries, infrastructure development of fishing harbours, bio diversity conservation and participatory forest management are the strategies adopted for the development of Agriculture and allied sectors in the state during the Tenth Five Year plan.
State Planning Board Thiruvananthapuram Government of Kerala